PENGARUH PROFITABILITAS TERHADAP HARGASAHAM PADA BANK PEMBANGUNAN DAERAHYANG TERDAFTAR DI BURSA EFEKINDONESIA PERIODE TAHUN 2013-2016 - Harsi Romli; Monica Kurniawan; Iwan Efriandy (Jurnal Ilmiah Ekonomi Global Masa Kini)
The financial performance is an important factor to attract investors to buy stocks. The stock value is determined by the price mechanism when the stock market is in progress based on the demand and supply of shares. This study was aimed to determine the effect of the financial performance by using ROA (Return on Assets), ROE (Return on Equity), and Operational Cost divided by Operational Income (BOPO) to the stock price of banking companies either partially or simultaneously. The sampling Development Bank listed on the Indonesia Stock Exchange (BEI) during the observation period of 2013-2016. The data used in this research was secondary data.The method of research analysis used was multiple linear regression analysis and assumption classical test. The research finding of F test showed simultaneously, the variable ROA, ROE, and BOPO had a significant influence on stock prices. Partially, with t test it showed that ROA variables had influence on stock price, but  ROE, and BOPO variables did not have influence on stock price.Keywords : ROA, ROE, BOPO, Closing Price